Research and Motion Analysis of Cutting Blade Mechanism of Copper Foil Shearing Machine - Ying Yueming (Jixie chuandong)
It is always a problem to improve the quality of copper foil shearing in PCB production.In order to research and develop copper foil shearing machine which has international competitiveness,taking the shearing mechanism of copper foil shearing machine designed by Rosenthal company in US as study object,the mechanism principle of shearing mechanism is descriped and the degree of freedom of mechanism is calculated.The motion analysis of shearing mechanism is carried out based on the methods of spatial mechanism kinematics and numerical calculation.Then,the analytic parameter formula of shearing mechanism cut point is deduced.The motion feature of shearing mechanism based on high speed and high cutting quality is proposed through the numerical experimentation and simulation experiment of shearing machine with 1500 copper foil breadth.The movement curve and controllable parameter which affects the performance of mechanism are obtained.The research contents can be taken as reference for the optimization of cutting blade mechanism design parameters.